Relativistic Fluid Dynamics Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 7-16, 1970 - Cattaneo, C. (C.I.M.E. Summer Schools, 2011)
Pham Mau Quam: Problèmes mathématiques en hydrodynamique relativiste.- A. Lichnerowicz: Ondes de choc, ondes infinitésimales et rayons en hydrodynamique et magnétohydrodynamique relativistes.- A.H. Taub: Variational principles in general relativity.- J. Ehlers: General relativistic kinetic theory of gases.- K. Marathe: Abstract Minkowski spaces as fibre bundles.- G. Boillat: Sur la propagation de la chaleur en relativité.